PEMODELAN GREENSHIELD TERHADAP HAMBATAN SAMPING PADA RUAS JALAN MP MANGKUNEGARA KOTA PALEMBANG - Yules Pramona Zulkarnain; Hariman Al Faritzie; Muhammad Andrean Jaya; Syahril Alzahri (LATERAL: Jurnal Teknik Sipil, 2025)
This study aims to analyze the impact of side friction on traffic performance along MP Mangkunegara Street, Palembang City, using the PKJI 2023 method and the Greenshields model. Observed side friction factors include parked/stopped vehicles, pedestrians, entering/exiting vehicles, and street vendors, with a very high intensity reaching 811.8 events/hour on Saturday and 890.4 events/hour on Tuesday. These conditions contribute to a significant reduction in free-flow speed and road capacity. Based on the Greenshields model analysis, the free-flow speed (Vf) decreased significantly from 38.833 km/h to 26.028 km/h, while the jam density (Dj) increased from 69.90 smp/km to 158.128 smp/km. Although the maximum flow (Qmax) increased due to rising density, the speed at maximum capacity declined. The peak-hour degree of saturation ranged from 0.44 to 0.78, indicating a level of service between B and D.